Preparation of symmetrical and asymmetrical multi-phenylene ring nonlinear optical materials with click chemical modifications and their properties. (19th November 2022) - Zhao, Yuzhen; Liu, Xinhua; Zhao, Xiangrong; Li, Qing; Zhao, Yang; Guo, Zhun; He, Zemin; Zhang, Huimin; Gao, Jianjing; Miao, Zongcheng
Abstract: A series of organic small molecules were synthesized using Sonagashira coupling reaction, which was post-functionally modified. The UV-VIS-NIR spectra showed that different click reagents can cause different degrees of redshift of the products, and the wide wave absorption can be achieved by using them together. Electrochemical studies show that the introduced click reagents increase the degree of conjugation, causing a reduction in energy bandwidth. Z-scan tests show that after the click, there is a mutual transition between saturable and anti-saturable absorption, which has different modulating effects on the nonlinear absorption of the material, which provides a good idea for the design of optical limiting molecular. Graphical abstract: Image 1